(2030 - التحول الهيكلي للإقتصاد الجزائري في إطار برنامج النمو الاقتصادي الجديد للفترة ( 2016: The structural transformation of the Algerian economy within the framework of the new economic growth program for the period (2016-2030) - بن داودية وهيبة, (Journal of North African Economies, 2025)
We aim through this study to analyze the indicators of the structural transformation of the Algerian economy before and after Algeria’s development of the new growth program for the period (2016-2030), and the conclusion was reached that the growth program faces a challenge represented in the decline of the state’s ability to maintain growth through public investments and the quality of its institutions. This leads to a slow structural transformation of the economy, as the non-hydrocarbon industry represents less than 15% of the added value of the economy, and productivity in general did not improve significantly, as the average total productivity growth reached only 1.11% during this period (1990-2018), which requires accelerate diversification.